Alimentos ancestrales en el aprendizaje - Cordones Cordones, Jhoana Mishell (2024)
Nowadays, society needs to promote the production of traditional crops and its consumption as an alternative for a healthy diet, so the recovery of ancestral foods such as corn, beans, quinoa, ocas, pumpkin, machica, morocho, paico, melloco and potatoes, contribute to the learning process by improving skills, abilities and behaviors, enhancing energy in academic performance to new generations with ancestral products. Consequently, students are lacking in the consumption of ancestral foods because they are unaware of the products that benefit learning and health, currently choose to consume processed food because it is easy to acquire in the same restaurants of the institution, also parents do not have time to prepare food with ancestral products for children.The objective of this research is to value ancestral foods for the improvement of learning in fifth grade children of the Mariscal Antonio José de Sucre School, 9 de Octubre Street, Saquisili Canton, school year 2023-2024. The methodology is based on an interpretative paradigm because it allows understanding the educational reality, the type of research is qualitative since it is oriented to a deep investigation based on the characteristics and benefits of ancestral foods in learning, the method was inductive due to the variables were analyzed from particular to general and the methodological design is based on a content analysis because information reduction processes were carried out to determine the categories. The results achieved are a diagnosis and reflections on ancestral foods as a form of expression of the customs and traditions of the people, they have wide benefits especially for their nutritional properties, which is why teachers mention that the way of eating has a great influence on learning. This research project contributes to raise awareness and value of ancestral foods in students to put into practice the consumption of nutritious food that favors the development of learning.